Polyethylene Glycol Mediated Osmotic Stress on Germination, Seedling Traits and Seed Metabolic Efficiency of Wheat (Bangladesh Agronomy Journal, 2023)
Germination characteristics, early seedling growth and seed metabolic efficiency of four wheat genotypes (BARI Gom 28, BARI Gom 29, BAW 1177 and ESWYT 29) were evaluated under 15% polyethylene glycol (PEG-6000) induced osmotic stress (-3 bar). Germination characteristics (germination rate, co-efficient of germination and germination vigor index), shoot and root length, shoot and root dry weight, and seed metabolic efficiency decreased under osmotic stress induced by PEG than control treatment. But the degree of reduction was different for various wheat genotypes. Genotype BAW 1177 showed the highest performance in respect to germination and early seedling traits at both control and PEG induced osmotic stress than other three genotypes. So, genotype BAW 1177 can be considered as relatively drought tolerant genotype.Bangladesh Agron. J. 2022, 25(2): 19-29